A Rare Case of Esophageal Dysphagia in Children: Aberrant Right Subclavian Artery. (20th January 2016) - Barone, Claudia; Carucci, Nicolina Stefania; Romano, Claudio
Abstract : Dysphagia is an impairment of swallowing that may involve any structures from the mouth to the stomach. Esophageal dysphagia presents with the sensation of food sticking, pain with swallowing, substernal pressure, or chronic heartburn. There are many causes of esophageal dysphagia, such as motility disorders and mechanical and inflammatory diseases. Infrequently dysphagia arises from extrinsic compression of the esophagus from any vascular anomaly of the aortic arch. The most common embryologic abnormality of the aortic arch is aberrant right subclavian artery, clinically known as arteria lusoria . This abnormality is usually silent. Here, we report a case of six-year-old child presenting to us with a history of progressive dysphagia without respiratory symptoms. A barium esophagogram showed an increase of the physiological esophageal narrowing at the level of aortic arch, while at esophagogastroduodenoscopy there was an extrinsic pulsatile compression of the posterior portion of the esophagus suggesting an extrinsic compression by an aberrant vessel. Angio-CT (computed tomography) scan confirmed the presence of an aberrant right subclavian artery.